Political theory and feminist social criticism - Ackerly, Brooke A. (Contemporary political theory., 2000)
Brooke Ackerly examines the methods by which Third World feminist activists have criticised society. She argues that their activities show how feminist theory can move beyond its theoretical impasse towards articulating a social criticism relevant to dealing with real world inequalities.